2020
DOI: 10.1161/strokeaha.119.026596
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Compared With Autoregulation-Oriented Blood Pressure Thresholds After Mechanical Thrombectomy for Ischemic Stroke

Abstract: Background and Purpose— Loss of cerebral autoregulation in the acute phase of ischemic stroke leaves patients vulnerable to blood pressure (BP) changes. Effective BP management after endovascular thrombectomy may protect the brain from hypoperfusion or hyperperfusion. In this observational study, we compared personalized, autoregulation-based BP targets to static systolic BP thresholds. Methods— We prospectively enrolled 90 patients undergoing endovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 38 publications
6
87
0
Order By: Relevance
“…In patients treated with EVT, BP control strategies in large ischemic stroke should be guided by the status of vessel recanalization and autoregulatory capacity, especially at 24 h after ischemic stroke onset. Consistent with our finding although with a different dCA monitoring measurement, a recent research suggested that continuous estimation of autoregulation-based treatment strategies after EVT was feasible and could provide a BP range for individual patients tailored to their own physiology [22]. In future, larger sample size research is needed to observe dCA status when changing BP level.…”
Section: Influence Factors On Clinical Outcome After Evtsupporting
confidence: 87%
See 1 more Smart Citation
“…In patients treated with EVT, BP control strategies in large ischemic stroke should be guided by the status of vessel recanalization and autoregulatory capacity, especially at 24 h after ischemic stroke onset. Consistent with our finding although with a different dCA monitoring measurement, a recent research suggested that continuous estimation of autoregulation-based treatment strategies after EVT was feasible and could provide a BP range for individual patients tailored to their own physiology [22]. In future, larger sample size research is needed to observe dCA status when changing BP level.…”
Section: Influence Factors On Clinical Outcome After Evtsupporting
confidence: 87%
“…Recently, numerous studies emphasize the significant predictive value of cerebrovascular reserve in ischemic stroke [21,22]. Reduced cerebrovascular reserve indicates that the arteriolar vasodilation activity is not able to maintain stable blood flow properly in the region of cerebral hypoperfusion [21,23,24].…”
Section: Choosing Dca As the Markermentioning
confidence: 99%
“…To this end, Anadani et al proposed a sub-analysis based on several key prognostic variables and found a possible varying effect of BP parameters among these characteristics (13). This tailored management is attracting growing attention, as shown by this recent study in which fixed BP thresholds were compared with autoregulation-oriented BP thresholds after EVT (38). By using Near-infrared spectroscopy-derived tissue oxygenation as a cerebral blood flow surrogate in response to mean arterial pressure (MAP) changes, an autoregulatory index was calculated to assess the BP ranges with autoregulation preservation (38).…”
Section: Discussionmentioning
confidence: 99%
“…This tailored management is attracting growing attention, as shown by this recent study in which fixed BP thresholds were compared with autoregulation-oriented BP thresholds after EVT (38). By using Near-infrared spectroscopy-derived tissue oxygenation as a cerebral blood flow surrogate in response to mean arterial pressure (MAP) changes, an autoregulatory index was calculated to assess the BP ranges with autoregulation preservation (38). The percent time with MAP above the upper limit of autoregulation was associated with worse functional outcomes at 3 months and more hemorrhagic transformations (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation